Pelatihan Menulis Resensi Buku sebagai Upaya Meningkatkan Literasi Kritis melalui Kolaborasi dengan Perpustakaan Daerah Aceh Tamiang - Nur Amelia; Muhammad Arif Fadhilah (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2026)
Critical literacy is an essential competency that should be strengthened to improve the quality of human resources in the information era. One effective approach to fostering critical literacy is through book review writing, which integrates reading, analyzing, evaluating, and communicating ideas in written form. This community engagement program aimed to enhance participants’ book review writing skills as an effort to strengthen critical literacy through collaboration with the Aceh Tamiang Regional Library. The program was conducted on May 26, 2026, involving students, university students, teachers, librarians, and community members. The program employed a Participatory Training approach consisting of preparation, material presentation, interactive discussions, book review writing practice, mentoring, and evaluation. Program evaluation was carried out through observation, assessment of participants’ book reviews using an evaluation rubric, and participant satisfaction questionnaires. The results indicated that participants demonstrated improved understanding of the concepts and techniques of book review writing and were able to produce more systematic, objective, and argumentative reviews. Participants also showed active engagement throughout the training sessions, while the overall level of satisfaction with the program was categorized as very high. Furthermore, the collaboration between the community engagement team and the Aceh Tamiang Regional Library strengthened the library’s role as a community-based literacy development center. Therefore, the book review writing training proved to be an effective strategy for enhancing critical literacy while fostering productive reading and writing habits within the community.